2008
DOI: 10.1002/ceat.200700447
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optimization in Chemical Processes Using Region Reduction Strategy and Control Vector Parameterization with an Ant Colony Optimization Algorithm

Abstract: Two different approaches of the dynamic optimization for chemical process control engineering applications are presented. The first approach is based on discretizing both the control region and the time interval. This method, known as the Region Reduction Strategy (RRS), employs the previous solution in its next iteration to obtain more accurate results. Moreover, the procedure will continue unless the control region becomes smaller than a prescribed value. The second approach is called Control Vector Paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Rajesh et al reached a value of 0.76237 using control profile approximation under the frame of ACO . Asgari and Mahmoud obtained a value of 0.76160 employing CVP with the ACO algorithm by embedding a region reduction strategy . Qian et al got a value of 0.761595, which is the best literature result close to the analytical result using the CVP method with an iterative genetic algorithm .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Rajesh et al reached a value of 0.76237 using control profile approximation under the frame of ACO . Asgari and Mahmoud obtained a value of 0.76160 employing CVP with the ACO algorithm by embedding a region reduction strategy . Qian et al got a value of 0.761595, which is the best literature result close to the analytical result using the CVP method with an iterative genetic algorithm .…”
Section: Resultsmentioning
confidence: 90%
“…This case is a benchmark dynamic optimization problem, which involves two state variables. The case has an analytical solution and the global optimum, thus, many researchers tested it as illustration of their approaches , , . The mathematical formulation of the case is stated as follows: true center min center J(u)= x2 ( tf ) center1normalsnormal.normaltnormal. center x · 1 =u center1 center x · 2 = x1 2 + u2 center1 center x(0)= [1,0]T …”
Section: Case Studiesmentioning
confidence: 99%
“…ASGARI and PISHVAIE [24] obtained the values of 0.122 and 0.1599, while ZHANG et al [21] and RAJESH et al [23] reported 0.1235 and 0.12904, respectively.…”
Section: Nonlinear Unconstrained Mathematical Systemmentioning
confidence: 92%
“…Place m ants (m = N x p) in each node. The algorithm proposed here follows the method of Zhang et al (2005) which placed the ants in each node at the difference of Asgari and Pishvaie (2008) which placed them in the nodes of the first column of time.…”
Section: Iaca Applied To Mpcmentioning
confidence: 99%